Community interventions for people with complex emotional needs that meet the criteria for personality disorder diagnoses: systematic review of economic evaluations and expert commentary. Issue 6 (15th November 2021) - Botham, Joe; Clark, Amy; Steare, Thomas; Stuart, Ruth; Oram, Sian; Lloyd-Evans, Brynmor; Jeynes, Tamar; Broeckelmann, Eva; Crawford, Mike; Johnson, Sonia; Simpson, Alan; McCrone, Paul
Abstract : Background: Diagnoses of personality disorder are prevalent among people using community secondary mental health services. Identifying cost-effective community-based interventions is important when working with finite resources. Aims: To assess the cost-effectiveness of primary or secondary care community-based interventions for people with complex emotional needs who meet criteria for a diagnosis of personality disorder to inform healthcare policy-making. Method: Systematic review (PROSPERO: CRD42020134068) of databases. We included economic evaluations of interventions for adults with complex emotional needs associated with a diagnosis of personality disorder in community mental health settings published before 18 September 2019. Study quality was assessed using the CHEERS statement. Results: Eighteen studies were included. The studies mainly evaluated psychotherapeutic interventions. Studies were also identified that evaluated altering the setting in which care was delivered and joint crisis plans. No strong economic evidence to support a single intervention or model of community-based care was identified. Conclusions: Robust economic evidence to support a single intervention or model of community-based care for people with complex emotional needs is lacking. The strongest evidence was for dialectical behaviour therapy, with all three identified studies indicating that it is likely to be cost-effective in community settings compared with treatment as usual. More robust evidence is required on the cost-effectiveness of community-based interventions on which decision makers can confidently base guidelines or allocate resources. The evidence should be based on consistent measures of costs and outcomes with sufficient sample sizes to demonstrate impacts on these.